Antioxidative Activities of Algal Keto Carotenoids Acting as Antioxidative Protectants in the Chloroplast. (26th February 2014) - Dambeck, Michael; Sandmann, Gerhard
Abstract Very diverse carotenoid structures exist in the photosynthesis apparatus of different algae. Among them, the keto derivatives are regarded the most antioxidative. Therefore, four different keto carotenoids, peridinin, fucoxanthin, siphonaxanthin and astaxanthin fatty acid monoesters, were isolated and purified from Amphidinium carterae, Phaeodactylum tricornutum, Caulerpa taxifolia and Haematococcus pluvialis, respectively. The carotenoids were assayed as inhibitors of photosensitizer initiated reactions or scavengers of radicals in the early events generating reactive oxygen species as starters for peroxidation and as protectants against the whole reaction chain finally leading to lipid peroxidation. These in vitro studies demonstrated the substantial antioxidative properties as indicated by the IC50 values of all four keto carotenoids with superior protection by astaxanthin fatty acid monoesters which were as effective as free astaxanthin and of peridinin against radicals. As an example, the in vivo relevance of fucoxanthin for protection of photosynthesis from excess light and from peroxidative agents was evaluated with intact cells. Cultures of P. tricornutum with decreased fucoxanthin content generated by inhibitor treatment were exposed to strong light or cumene hydroperoxyde. In each case, oxidation of chlorophyll as marker for damaging of the photosynthesis apparatus was less severe when the fucoxanthin was at maximum level.